Communication Strategies in Synchronous and Asynchronous Media - Amalia Rosaline; Frimadhona Syafri; Zulfa Sakhiyya (Universitas Negeri Semarang, 2023)
This study compares the communication strategies employed in synchronous and asynchronous media during the learning of English. E-learning has been employed more frequently. This condition enables English subjects to be taught and learned in a setting without face-to-face interaction. E-learning is available in both synchronous and asynchronous modes. Based on the communication methods that arose in both modes, this study was done to present the emergence of communication strategies in both media. The present study involved 36 university students who were enrolled in a teaching methodology course and one lecturer. Specifically, the data were gathered through WhatsApp Group observation and Zoom interviews. The discussion of the study was presented using an explanatory format because it was a qualitative study. From the study, there were 3 types of communication strategies found in synchronous (Zoom), namely codeswitching (87%), time-gaining (13%), and foreignizing (0,3%). While in asynchronous mode using WhatsApp Group, codeswitching (12,5%) and literal translation (87,5%) were found. and synchronous media (Zoom). It was found that the students’ engagement in the WhatsApp group was higher (82%) than was found in Zoom (18%). However, the attitude and awareness of the students also played a significant role in the development of the communication strategies. This study contributes to the research on communication strategies found not only in oral form but also in written form and can be a consideration to promote the teaching of communication strategies.